Aerodynamics for engineers - Bertin, John J., 1938; Cummings, Russell M (Russell Mark) (Cambridge University Press, 2022)
"The study of aerodynamics is a challenging and rewarding discipline within aeronautics since the ability of an airplane to perform (how high, how fast, and how far an airplane will fly, such as the F-15E shown in Fig. 1.1 ) is determined largely by the aerodynamics of the vehicle. However, determining the aerodynamics of a vehicle (finding the lift and drag) is one of the most difficult things you will ever do in engineering, requiring complex theories, experiments in wind tunnels, and simulations using modern highspeed computers. Doing any of these things is a challenge, but a challenge well worth the effort for those wanting to better understand aircraft flight"